Finding Cases of Hepatitis C for Treatment Using Automated Screening in the Emergency Department is Effective, but What Is the Cost?. (14th October 2022) - Prince, David Stephen; Girolamo, Julia Di; Pipicella, Joseph Louis; Bagatella, Melissa; Kayes, Tahrima; Alvaro, Frank; Maley, Michael; Foo, Hong; Middleton, Paul MacConachie; Levy, Miriam Tania
Abstract : Case detection remains a major challenge for hepatitis C virus (HCV) elimination. We have previously published results from a pilot of an emergency department (ED) semiautomated screening program, SEARCH; Screening Emergency Admissions at Risk of Chronic HCV. Several refinements to SEARCH have been developed to streamline and reduce cost. All direct costs of HCV testing until direct-acting antiviral (DAA) therapy initiation were calculated. Cost was assessed in 2018 Australian Dollars. A cost analysis of the initial program and refinements are presented. Sensitivity analysis to understand impact of variation in staff time, laboratory test cost, changes in HCV antibody (Ab) prevalence, RNA positivity percentage, and rate of linkage to care was conducted. Impact of refinements (SEARCH (2)) to cost is presented. The total SEARCH pilot, testing 5000 patients was estimated to cost 110, 549.52 (range 92, 109.79–129, 581.24) comprising of 68, 278.67 for HCV Ab testing, 21, 568.99 for follow-up and linkage to care of positive patients and 20, 701.86 to prepare HCV RNA positive patients for treatment. Internal program refinements resulted in a 25% cost reduction. Following refinements, the cost of HCV antibody screening was 8.46 per test and the total cost per positive HCV Ab, positive HCV RNA, and per treated patient were 611.77, 2, 168.64, and 3, 566.11, respectively. Our sensitivity analysis indicates costs per HCV case found are modest so long as HCV Ab prevalence was at least 1%. ED screening is an affordable strategy for HCV case detection and elimination.